Fabrication and characterisation of cellulose nanocrystals from microcrystalline cellulose by esterification and ultrasound treatment. (1st November 2018) - Jiang, Longwei; Yang, Jingde; Wang, Qian; Ren, Lili; Zhou, Jiang
Abstract : In the present work, needle‐shaped cellulose nanocrystals (CNCs) were prepared from commercial microcrystalline cellulose (MCC) through esterification and ultrasound treatment. The prepared CNCs were characterised by using Fourier transform infrared, degree of substitution (DS), dynamic light scattering, scanning electron microscopy and X‐ray diffraction. The results revealed that the ultrasound disintegration of MCC was significantly improved after the esterification with maleic anhydride and the ultrasound treatment did not affect DS of the CNCs. With increasing power of the ultrasound treatment, smaller CNCs with narrower size distribution could be obtained. Average diameter and length of the CNCs could reach ∼14 and ∼180 nm, respectively. Furthermore, the crystal structure of cellulose was not changed during the esterification and ultrasound treatment and crystallinity of the CNCs increased comparing with MCC.